The “New Political Economy”: Recent Books by Allen Drazen and by Torsten Persson and Guido Tabellini - Saint-Paul, Gilles (Journal of Economic Literature, 2000)
The last fifteen years have seen an explosion of contributions in the field of political economy. Two new books, Political Economy in Macroeconomics by Allan Drazen and Political Economy: Explaining Economic Policy by Torsten Persson and Guido Tabellini, organize this literature and evaluate what has been learned. Drazen mostly focuses on applications for macroeconomic policy, while Persson and Tabellini focus on the various tools that can be used to analyze the political process, and the institutional details of decision-making.